Neutrinos from accreting neutron stars - Anchordoqui, Luis A. (2003)
The magnetospheres of accreting neutron stars develop electrostatic gaps with huge potential drops. Protons and ions, accelerated in these gaps along the dipolar magnetic field lines to energies greater than 100 TeV, can impact onto the surrounding accretion disk. A proton-induced cascade develops, and charged pion decays produce ν emission. With extensive disk shower simulations using DPMJET and GEANT4, we have calculated the resulting ν spectrum. We show that the spectrum produced out of the proton beam is a power law. We use this result to propose accretion-powered X-ray binaries (with highly magnetized neutron stars) as a new population of pointlike ν sources for kilometer-scale detectors such as ICECUBE. As a particular example, we discuss the case of A0535+26. We show that ICECUBE should find A0535+26 to be a periodic ν source, one for which the formation and loss of its accretion disk can be fully detected. Finally, we comment briefly on the possibility that smaller telescopes such as AMANDA could also detect A0535+26 by folding observations with the orbital period.